2022
DOI: 10.1111/opn.12456
|View full text |Cite
|
Sign up to set email alerts
|

In‐hospital medical complication in older people after spine surgery: A scoping review

Abstract: Objective Worldwide, older people are suffering from lumbar degenerative disease at an annual rate of 266 million. Although spine surgeries restore mobility, reduce pain and resolve neurological damage, these procedures can place older persons at high‐risk for medical complications due to multiple comorbid conditions that are often present in this population. However, the prevalence of complications occurring in older people prior to discharge is unknown. Postoperative medical complications lead to increased h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 65 publications
0
2
0
1
Order By: Relevance
“…The co‐occurrence network analysis was used to examine the co‐occurrence of chronic stressors that were somewhat or very upsetting. The network was built based on the Fruchterman–Reingold algorithm using Gephi software (Bastian et al, 2009; Strayer et al, 2022). The goals of this algorithm are to (1) distribute the nodes evenly in the frame, (2) make the lengths of edges uniform, (3) minimize the number of edge crossings, and (4) reflect inherent symmetry (Fruchterman & Reingold, 1991; Gajdoš et al, 2016).…”
Section: Methodsmentioning
confidence: 99%
“…The co‐occurrence network analysis was used to examine the co‐occurrence of chronic stressors that were somewhat or very upsetting. The network was built based on the Fruchterman–Reingold algorithm using Gephi software (Bastian et al, 2009; Strayer et al, 2022). The goals of this algorithm are to (1) distribute the nodes evenly in the frame, (2) make the lengths of edges uniform, (3) minimize the number of edge crossings, and (4) reflect inherent symmetry (Fruchterman & Reingold, 1991; Gajdoš et al, 2016).…”
Section: Methodsmentioning
confidence: 99%
“…Interestingly, Carreon et al demonstrated that, specifically for lumbar instrumentation due to degenerative diseases, the risk threshold for perioperative complications seems to be 75 years and older, largely attributable to the increased prevalence of comorbidities in this age bracket ( Carreon et al, 2003 ). A recent review and meta-analysis assessing outcomes of spinal surgery for degenerative conditions in advanced age revealed that patients over 80 years, given their elevated risk profile, are more susceptible to complications than their younger counterparts ( Strayer et al, 2022 ). Aligned with these findings, our study also revealed that patients aged 65–79 years, with their moderate comorbidity profile, had an AE rate of 8.1%.…”
Section: Discussionmentioning
confidence: 99%
“…Особливістю зарубіжних публікацій з проблем хірургії, зокрема присвячених хірургії хребта, є вільніше обговорення помилок та ускладнень порівняно з вітчизняними науковими працями [21][22][23][24]. Проте низка критичних моментів залишаються невисвітленими.…”
Section: вступunclassified